A Standardized and Interoperable Approach for Multi-Vendor DAS–DIS Integration in Continuous Emission Monitoring Systems - Hery Herawan (Asosiasi Dosen Muda Indonesia, 2026)
The increasing complexity of industrial emissions and the limitations of conventional monitoring systems have created an urgent need for reliable, real-time, and interoperable emission monitoring solutions. In Continuous Emission Monitoring Systems (CEMS), the integration of heterogeneous data from multi-vendor Data Acquisition Systems (DAS) remains a major challenge, particularly in relation to data consistency, interoperability, and regulatory compliance. Objective: This study aims to develop an integrated DAS–DIS framework that standardizes data processing and communication across heterogeneous industrial environments. Method: This research employed a system engineering approach using a prototype-based development method. Data sources included regulatory documents, technical standards, and simulated emission datasets in CSV, XML, and JSON formats. The system was designed using a JSON-based Unified Data Model (UDM), supported by ISO 8601 timestamps, quality codes, HMAC-based digital signatures, and hybrid HTTP–MQTT communication protocols. Functional testing and simulation were conducted to evaluate data transformation, validation, and transmission. Findings: The results show that the proposed system can transform heterogeneous DAS outputs into a consistent and standardized structure while maintaining data integrity and reliability. JSON schema validation and digital signatures support secure data exchange, while the hybrid communication architecture enables both regulatory reporting and real-time monitoring. Implications: The proposed framework can improve interoperability, reliability, and operational efficiency in industrial emission monitoring systems, while also supporting regulatory compliance and data-driven environmental management. Originality: This study offers an integrated and application-oriented framework that combines data standardization, communication architecture, and validation mechanisms within a single system specifically designed for multi-vendor CEMS integration.